METHODOLOGY FOR STUDYING CHINGIZ AITMATOV’S STORY ABOUT “THE WHITE SHIP” - Mubora Omanova (Galaxy International Interdisciplinary Research Journal, 2024)
The work of Chingiz Aitmatov, the great representative of the fraternal Kyrgyz people, the favorite writer of world readers, is distinguished by a unique interpretation and high artistry of universal ideas. One of the factors ensuring the success of the writer’s works is that at that time he raised pressing problems, was imbued with deep realism and high ideas of the nationality. The article discusses how Chingiz Aitmatov might study “White Ship”